The COMTp.Val158Met polymorphism and cognitive performance in adult development, healthy aging and mild cognitive impairment - Degen, Christina; Zschocke, Johannes; Toro, Pablo; Hildesheim, Christine; Wahl, Hans-Werner; Schönknecht, Peter; Schröder, Johannes (Dementia and geriatric cognitive disorders, 2016)
The impact of genetic polymorphisms on cognition is assumed to increase with age as losses of brain resources have to be compensated for. We investigate the relation of catechol-O-methyltransferase (COMT)p.Val158Met polymorphism and cognitive capacity in the course of adult development, healthy aging and the development of mild cognitive impairment (MCI) in two birth cohorts of subjects born between 1930 and 1932 or between 1950 and 1952. Methods: Thorough neuropsychological assessment was conducted in a total of 587 participants across three examination waves between 1993 and 2008. The COMT genotype was determined as a restriction fragment length polymorphism after PCR amplification and digestion with NlaIII. Results: Significant effects of the COMTp.Val158Met polymorphism were identified for attention and cognitive flexibility in the younger but not the older cohort. Conclusion: These results confirm the importance of the COMTp.Val158Met genotype on tasks assessing attention and cognitive flexibility in midlife but not in healthy aging and the development of MCI. Our findings suggest that the influence of COMT changes as a function of age, decreasing from midlife to aging.
Gesehen am 11.01.2021
Published online: October 22, 2015